DIGITAL BASED LEARNING MANAGEMENT IN INCREASING COMPETITIVENESS - Eko Julianto Wibowo; Agus Zaenul Fitri; Sulistyorini (As-Sulthan Journal of Education, 2026)
The transformation of the work ecosystem into the digital realm has brought about fundamental shifts in various sectors. The digital ecosystem influences the increase in school competitiveness with digital learning strategies by teachers and students in improving the quality of education that has been set in the curriculum which can be monitored from the performance of teachers, staff and student achievement at SD Muhammadiyah Blitar. Through a qualitative approach using interviews and document studies, this study highlights how digital culture plays a crucial role in boosting school competitiveness and quality as reflected in teacher performance and student achievement. The success of curriculum implementation in this ecosystem is highly dependent on educators' mastery of digital literacy, where teachers are required to proactively develop their professional competencies to be able to utilize technology as an effective learning instrument. Ultimately, this digitalization effort is not merely following trends, but a strategic step to expand access to education while equipping students with relevant skills needed in an increasingly globally connected world.